The political situation in Iraq, and the problem of Kurdish autonomy in 1960-1970 (Journal of Oriental Studies, 2016)
This article addresses problems of Kurdish autonomy and the ways of its resolving in the context of the situation in Iraq in 1960-1970 on the basis of historical juridical documents.
Keywords: аgreement; autonomy